2015
DOI: 10.17656/jzs.10440
|View full text |Cite
|
Sign up to set email alerts
|

Soil Pollution Assessment from Industrial Area of Erbil City

Abstract: Present study assessed soil pollution by heavy metals and spent oil in three industrial areas of Erbil City. Soil pH ranged from 7.53±0.017 to 8.25±0.012 and EC was ranged between 103±0.882 and 465±9.955. Soils textures were loamy sand for south industry, sandy for oil selling area and north industry while loamy for control soil. The ranges of Pb, Zn and Ni were between 1.26±0.069 and 17.472±0.058; 1.439±0.006 and 3.078±0.003, and 0.399±0.061 and 0.982±0.048 ppm, respectively. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Increasing greenhouse total soil Pb concentration during second sampling dates, might be because of leaching lead from oil refinery projects and percolation to groundwater that cause increasing greenhouse soil total Pb concentration through irrigation. These results were in accordance to previous studies (19,44). Previous study concluded that, lead concentration was increased after fertilization, and increased two times after harvesting, as well as, atmospheric deposition, manure, and sludge application (31).…”
Section: Resultssupporting
confidence: 93%
“…Increasing greenhouse total soil Pb concentration during second sampling dates, might be because of leaching lead from oil refinery projects and percolation to groundwater that cause increasing greenhouse soil total Pb concentration through irrigation. These results were in accordance to previous studies (19,44). Previous study concluded that, lead concentration was increased after fertilization, and increased two times after harvesting, as well as, atmospheric deposition, manure, and sludge application (31).…”
Section: Resultssupporting
confidence: 93%
“…Erbil is located in northern Iraq and is situated 414 m above sea level at longitude 43º15ʹ E and latitude 35º11ʹ N. The Erbil climate is characterized by cold winters, mild in spring and hot summers, somehow similar to the Irano-Turanian type of the semi-arid zones [22]. In the present study, two different study sites were selected.…”
Section: Study Sitesmentioning
confidence: 99%
“…Concerning the railroad transport, the pollution depends on an engine type. Diesel locomotives use fuel combustion, similarly to the road vehicles, they also release polycyclic aromatic hydrocarbons in contrary, electric locomotives are considered as environmentally friendly, however, the presence of the railroad itself could significantly increase metal concentrations in nearby soils, in addition, particle abrasion from wheels, tracks and pantographs can get metals into aerosols and pollute the wider railway, surroundings cleaning bays and railway sidings are also heavily polluted areas; concentrations of Pb, Cu, Zn, Fe, Cr and Hg in soils could be several times higher than at relatively clean control areas outside studied sites (8).Heavy metals emission sources in the environment are both; natural ,such as soil ,rock erosion and dust or anthropogenic, such as industrial activities, mining, rapid organization, transportation and pesticides (6). Rapid economic development has led to rapid expansion of the highway transportation industry which has resulted in increases in the emissions of such contaminants as heavy metals, roadside soils tend to accumulate pollutants directly emitted from vehicle exhaust, and soils can easily come into contact with pedestrians and inhabitants near the roads, either via inhalation of suspended particles or by direct contact exposure to inhalable emissions from roadways has been implicated as a threat to human health and is associated with an increased risk of respiratory illness (22).…”
Section: Introductionmentioning
confidence: 88%
“…The topsoil is calcareous with a 1-2% organic matter and exists in areas with hot-dry summers and cold rainy winters (4). The Erbil climate is somehow similar to the Irano-Turanian type of the semi-arid zones, characterized by cold winters, mild-growing periods in spring and hot summers (8). The local public transportation for Erbil city is provided by buses and taxis.…”
Section: Study Areamentioning
confidence: 98%